1980
DOI: 10.1149/1.2129742
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Transmission Electron Microscope Techniques Applied to Device Failure Analysis

Abstract: Special techniques have been developed for routine preparation of transmission electron microscope samples from integrated circuit devices. These methods, which are described and illustrated in this paper, are the preparation of replicas of fractured multilayer structures, vertical cross sections, horizontal cross sections, and feature enhancement on cross-section samples through the use of special staining and etching treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…An amorphous layer is always present at the surfaces of samples prepared by these methods. Its thickness can be reduced by finishing the ion-beam thinning at very low angles and voltages, but it cannot be eliminated entirely, see for example [2]. An alternative technique is the recently developed and entirely mechanical "tripod" method [3] in which increasingly fine polishing media are used to produce a low-angle wedge of material, and appears in most cases to be essentially free of amorphous overlayers and dirt.…”
Section: The Samplementioning
confidence: 99%
“…An amorphous layer is always present at the surfaces of samples prepared by these methods. Its thickness can be reduced by finishing the ion-beam thinning at very low angles and voltages, but it cannot be eliminated entirely, see for example [2]. An alternative technique is the recently developed and entirely mechanical "tripod" method [3] in which increasingly fine polishing media are used to produce a low-angle wedge of material, and appears in most cases to be essentially free of amorphous overlayers and dirt.…”
Section: The Samplementioning
confidence: 99%
“…The region of interest is typically within one micron of the surface, and the microstructure usually exhibits a strong depth dependence. There are numerous papers available that describe different techniques for preparing cross-section TEM specimens from metals or ceramics, including Spurling and Rhodes (19721, Abrahams and Buiocchi (1974), Sheng and Marcus (1980), Bravman and Sinclair (1984), Newcomb et al (19851, Zinkle and Sindelar (19861, Santella et al (19881, Sklad (19881, Summerville and Posthill (19891, and Romano et al (1989). For monolithic ionimplanted ceramics, the standard cross-section preparation procedure involves the following steps, which are outlined in Figure 1: First, the ion-implanted specimen is glued face-to-face to another polished specimen (either implanted or nonimplanted).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional TEM specimens of multilayer thin film structures, similar t6 those of electronic or dielectric materials, are generally prepared by mechanical thinning and subsequent ion milling, as first described by Abrahams and Buiocchi (1974), and further developed by various groups (Baxter and Stobbs, 1985;Garulli et al, 1985;Holloway and Sinclair, 1987;Sheng and Marcus, 1980). Special techniques such as mechanical dimpling prior to ion milling (Bravman and Sinclair, 1984;Shinde and De Jonghe, 1986; Vanhellemont et al, 1983Vanhellemont et al, , 1988, the application of beam shields to the specimen stage (Chang et al, 1988;Helmersson and Sundgren, 19861, and the use of masks over the specimens (Santella et al, 1988) to prevent subsequent preferential ion beam thinning have been reported.…”
Section: Introductionmentioning
confidence: 99%